2012
DOI: 10.1016/j.archoralbio.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Bmp signalling in filiform tongue papillae development

Abstract: Objective Tongue papillae are critical organs in mastication. There are four different types of tongue papillae; fungiform, circumvallate, foliate, and filiform papillae. Unlike the other three taste papillae, non-gustatory papillae, filiform papillae cover the entire dorsal surface of the tongue and are important structures for the mechanical stress of sucking. Filiform papillae are further classified into two subtypes with different morphologies, depending on their location on the dorsum of the tongue. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…These features have been examined via electron microscopy studies, with the formation of the tongue coating found to be dependent on the physiological state of filiform papillae ( 4 ). For example, the filiform papillae within the cuticle of a thick coating are prominent and dense, while the cuticle of a thin coating is obviously atrophied ( 5 ). The epidermis of the tongue dorsum contains a highly specialized epithelium consisting of several stratified cell layers called squamous epithelium, with these epithelial cells continuously renewed by the mitotic activity of stem cells within the basal layer ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…These features have been examined via electron microscopy studies, with the formation of the tongue coating found to be dependent on the physiological state of filiform papillae ( 4 ). For example, the filiform papillae within the cuticle of a thick coating are prominent and dense, while the cuticle of a thin coating is obviously atrophied ( 5 ). The epidermis of the tongue dorsum contains a highly specialized epithelium consisting of several stratified cell layers called squamous epithelium, with these epithelial cells continuously renewed by the mitotic activity of stem cells within the basal layer ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…8C ), Wnt/β-catenin 38 , 40 , 50 52 (Fig. 8D ), TGF-β/BMP 36 , 46 , 53 , 54 (Fig. 8E ), Notch 55 57 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Non‐gustatory filiform papillae are important for helping to grip food, drawing food to the esophagus, cleaning the mouth, and spreading saliva. Although filiform papillae cover the entire dorsal surface of the tongue, it has been shown that there are morphological differences between the filiform papillae in the intermolar eminence and those in anterior region, which are regulated by Bmp signaling (Beites et al, ; Kawasaki et al, ). In addition to the differences between the anterior tongue and the intermolar eminence, our results suggest that there is another distinct developmental mechanism for the mesio‐lateral axis of the dorsum tongue, which is regulated by Ikkα and Irf6 .…”
Section: Discussionmentioning
confidence: 99%